THE ROLE OF DIGITAL MINDSET AND TECHNOLOGICAL PROFICIENCY ON APPARATUS READINESS IN FACING DIGITAL TRANSFORMATION THROUGH DIGITAL ENGAGEMENT AT THE EDUCATION AND CULTURE OFFICE OF BANDAR LAMPUNG CITY - Dwi Wahyuningsih; Febrianty; Reza Hardian Pratama (Yayasan Multidimensi Kreatif, 2026)
This study examines how the digital mindset and technological proficiency of the civil service apparatus influence their readiness to face digital transformation through active engagement in utilizing digital technology at the Education and Culture Office of Bandar Lampung City. Employing a quantitative approach with the SEM-PLS model on a sample of over 100 respondents, the results indicate that an open and optimistic digital mindset towards technology directly enhances apparatus readiness, as does proficiency in using digital applications and systems. Digital engagement serves as a crucial mediating bridge that strengthens these relationships, with all variables rated highly by the respondents and the analytical model meeting stringent validity and reliability standards. These findings provide practical implications in the form of recommendations for hybrid mindset-technology training and mandatory digital platform policies to accelerate digital transformation within local government agencies.